Semantic Knowledge Management: The Marriage Of Semantic Web And Knowledge Management - Edi, Edi (Jurnal TIMES, 2014)
Knowledge management (KM) has been known as important field in managing tacit and explicit knowledge in organization. The challenges that have been faced by KM such as information overload, inefficient keyword searching, etc need to be tackled by using semantic web technology. The purpose of this study is to analyze how the integration of KM and semantic web, which is so- called â€œsemantic knowledge managementâ€ could be used to bridge the shifting from current Web 2.0 to future Web 3.0. Literature review is used as a research method in this paper. The research is limited to explicit knowledge being processed by machine.